2020
DOI: 10.1186/s11658-020-00210-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-144-3p inhibits cell proliferation of colorectal cancer cells by targeting BCL6 via inhibition of Wnt/β-catenin signaling

Abstract: Background: It has been shown that miR-144-3p regulates cell proliferation, apoptosis, migration and invasion in various cancers. However, the function and expression of miR-144-3p in colorectal cancer (CRC) remained obscure. Methods: Immunohistochemical (IHC) staining was performed to investigate the protein expression of BCL6 in CRC tissues. The effect of BCL6 and miR-144-3p on CRC cells was explored through methylthiazolyl tetrazolium (MTT) assay, colony formation and cell cycle assays. Luciferase reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…MicroRNAs (miRNAs, miRs) are endogenously expressed small non-coding RNAs that generally regulate gene expression by binding to the 3ʹ untranslated region (3ʹ-UTR) of their targets, resulting in silencing [ 13 ]. Numerous studies have shown that they play crucial roles in human cancer development, with particular impact on cancer cell proliferation, differentiation, cell cycle and apoptosis [ 14 16 ]. Thus, they’re involved in regulating the progression and metastasis of tumors [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs, miRs) are endogenously expressed small non-coding RNAs that generally regulate gene expression by binding to the 3ʹ untranslated region (3ʹ-UTR) of their targets, resulting in silencing [ 13 ]. Numerous studies have shown that they play crucial roles in human cancer development, with particular impact on cancer cell proliferation, differentiation, cell cycle and apoptosis [ 14 16 ]. Thus, they’re involved in regulating the progression and metastasis of tumors [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sun and co-workers [ 21 ] identified miR-144-3p as a new biomarker for CRC diagnosis and response to treatment. miR-144-3p was found downregulated and associated with CRC pathological stages in CRC patients.…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%
“…Previous studies revealed that BCL6 is involved in the control of cell cycle progression and differentiation [ 22 , 23 ]. Indeed, miR-144-3p/ BCL6 co-operate to inhibit cellular proliferation, development, and progression of CRC by interfering with c-myc and cyclin D1 expression [ 21 ] ( Table 1 ).…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%
“…Survivin and Bcl-2 family proteins exhibit their anti-apoptotic functions in tumor cells. Additionally, a recent investigation revealed that miR-144-3p could inhibit proliferation in CRC cells by targeting B-celll ymphoma 6 (BCL6) via the inhibition of Wnt/β-catenin signaling [28]. Iwaya et al [29] reported that mTOR is the direct target of miR-144 in CRC cells, and miR-144 suppression of mTOR led to the inhibition of cell proliferation.…”
Section: Microrna-144 In Cancer Proliferation and Apoptosismentioning
confidence: 99%